KEPUTUSAN PEMBELIAN DI TINJAU DARI INOVASI, HARGA DAN BRAND IMAGE (PADA MOBIL TOYOTA CALYA DI NASMOCO SLAMET RIYADI SURAKARTA) - Sontyan Iqbal Wibisono; Djumali Djumali; Bambang Mursito (JURNAL ILMIAH EDUNOMIKA, 2020)
The purpose of this study was to determine whether there is a significant influence between the innovation variable, price, and brand image on purchasing decisions. In addition, it is also to determine whether there is a significant simultaneous influence and which variable is the most dominant in influencing purchasing decisions on the Toyota Calya Car at Nasmoco Slamet Riyadi Surakarta. The method used is descriptive quantitative method. The population in this study amounted to 75 consumers and the sample used was 75, where the sampling technique used saturated sampling (census). The data used are primary data and secondary data with data collection techniques: observation, questionnaires, interviews, documentation and literature study. The data analysis technique in this study used multiple linear tests. The results of the study can be concluded that: The results of the study can be concluded that: 1) There is an effect of innovation, price, and brand image simultaneously on purchasing decisions on the Toyota Calya Car Di Nasmoco Slamet Riyadi Surakarta. 2) There is an influence of innovation on purchasing decisions at Toyota Calya Car in Nasmoco Slamet Riyadi Surakarta 3) There is an effect of price on purchasing decisions on Toyota Calya cars at Nasmoco Slamet Riyadi Surakarta, 4) There is an influence of brand image on purchasing decisions on Toyota Calya cars in Nasmoco Slamet Riyadi Surakarta Keywords: Purchase Decision, Innovation, Price, and Brand Image